Efektivitas Pelatihan Print Referencing Guna Meningkatkan Ketrampilan Pengajaran Literasi Dini pada Guru Prasekolah - Karisma Riskinanti (PG-PAUD Trunojoyo, 2014)
Early childhood curriculum mention about early literacy teaching literacy in the form of recognition of letters and numbers in accordance with the stages of child development. Through a training needs assessment result in mind that the skills and knowledge of teachers TK about teaching early literacy in accordance with sub-optimal child development stages. This makes preschool teachers need to improve early literacy teaching skills. Training in the use of this method of print referencing is donein an attempt to add the teaching skills of preschool teachers as facilitators of learning early literacy. The training participants were 10 kindergarten teachers. Data obtained from interviews, observations before and after training, as well as teacher knowledge test. Observation result were analyzed with statistical data analysis techniques of non parametic wilcoxon signed rank test with test scores observation of teaching skills of the participants before and after training. Analysis of the results obtaine by the value of significance (2-tailed) was 0,008 0,05. From these results in significant differences between teachers skill in early literacy instruction before and after training. So it can be concluded that an effective training method print referencing to improve teachers skills ini teaching early literacy. Whereas the results of knowledge there is no significant difference. The effectiveness of this method can be significant because it is influenced by intrinsic and extrinsic motivation of trainees.